Key factors on the spatial structure of smart city in an ICT dominated era (case study: Greater Mashhad) - Reza Akbari; Zahra Eidy (Ain Shams Engineering Journal)
Although the industrial revolutions including steam engine, electricity and Information and Communication Technology (ICT) have changed the spatial structure of cities, the key factors on the Spatial Structure of Smart City in an ICT Dominated Era are not well understood. Especially, in the case of Mashhad city, where the spatial structure is historically tied to the shrine, but due to urban mismanagement, it could not provide the necessary functions. This quantitative and exploratory study in Greater Mashhad, by using an 18-member Delphi team of experts, shows 14 factors influence the Spatial Structure of Smart City in an ICT Dominated Era and lets to understand better the effect of industrial revolutions on urban spatial structure. This helps urban planners in the fair distribution of services and facilities in the urban spatial structure.